Virtual interdisciplinary collaboration during the COVID-19 pandemic: pain and joy in an international joint university - Lu, Jinjin (Frontiers in Psychology, 2023)
Background The COVID-19 pandemic has brought interdisciplinary academics and research students many uncertainties and challenges in adapting to new communication styles. Compared with other academics in the same field, interdisciplinary academics might face more challenges in transitioning from traditional face-to-face communication to virtual communication. Objective This study aimed to explore the pain and joy of using Western and Chinese localized communication channels in experienced interdisciplinary academics (N = 10) and young research students (N = 14) during the pandemic. Among them, 14 are Europeans and 10 are Chinese. Method Meeting records and participants' reflective writing were used as qualitative data. Results We identified five key themes: two were tied to personal and behavioral issues, two were involved in management issues, and one dealt with topic choice issues. Conclusion Considering that virtual interdisciplinary teamwork is likely to continue in the post-pandemic period, it is necessary to implement measures such as technical training and voluntary assistants to help alleviate some of the issues that make virtual meetings difficult for participants. Study limitations and future directions are also discussed.